Pharmacoeconomic - Weiam A. Harwan; Maggie M. Abbassi; May M. El-Attar; Samar F. Farid (Faculty of Pharmacy, Cairo University, 2014)
Community-acquired pneumonia (CAP) is a serious and widespread infection due to its high incidence, morbidity, mortality and increased healthcare costs. This study aimed at investigating antibiotic combination regimen containing fluoroquinolone (Group A) and antibiotic combination regimen not containing fluoroquinolone (Group B) in terms of effectiveness parameters and direct medical costs associated with treatment of CAP patients admitted to Intensive Care Unit (ICU). This study was designed as retrospective and prospective observational studies including CAP patients admitted to the Respiratory ICU. The patients' files were collected and the effectiveness parameters of outcomes were compared on admission and on discharge. Effectiveness and costs analyses between antibiotic regimens either containing or not containing fluoroquinolone were performed. A total of 16 patients were enrolled in our retrospective study; (Group A) included 7 patients, while (Group B) included 9 patients. The prospective study included 30 patients; (Group A) included 13 patients and (Group B) included 17 patients. There was non-significant difference in the number of days in ICU between the two groups with a trend to shorter length of stay in ICU in (Group B) compared to (Group A) in both retrospective and prospective studies. Cost analysis showed that there was non-significant difference with a trend to lower direct medical costs in (Group B) which resulted in cost savings of (L.E) 1277 and (L.E) 816 for retrospective study and prospective study respectively. In conclusion, regimens containing or not containing fluoroquinolone did not show a significant increase in either effectiveness or costs of CAP treatment in the ICU.